Corruption of the Fas Pathway Delays the Pulmonary Clearance of Murine Osteosarcoma Cells, Enhances Their Metastatic Potential, and Reduces the Effect of Aerosol Gemcitabine - Gordon, Nancy (Clin Cancer Res, 2007)
PURPOSE: Pulmonary metastases continue to be a significant problem in osteosarcoma. Apoptosis dysfunction is known to influence tumor development. Fas (CD95, APO-1)/FasL is one of the most extensively studied apoptotic pathways. Because FasL is constitutively expressed in the lung, cells that express Fas should be eliminated by lung endothelium. Cells with low or no cell surface Fas expression may be able to evade this innate defense mechanism. The purpose of these studies was to evaluate Fas expression in osteosarcoma lung metastases and the effect of gemcitabine on Fas expression and tumor growth. EXPERIMENTAL DESIGN AND RESULTS: Using the K7M2 murine osteosarcoma model, Fas expression was quantified using immunohistochemistry. High levels of Fas were present in primary tumors, but no Fas expression was present in actively growing lung metastases. Blocking the Fas pathway using Fas-associated death domain dominant-negative delayed tumor cell clearance from the lung and increased metastatic potential. Treatment of mice with aerosol gemcitabine resulted in increased Fas expression and subsequent tum or regression. CONCLUSIONS: We conclude that corruption of the Fas pathway is critical to the ability of osteosarcoma cells to grow in the lung. Agents such as gemcitabine that up-regulate cell surface Fas expression may therefore be effective in treating osteosarcoma lung metastases. These data also suggest that an additional mechanism by which gemcitabine induces regression of osteosarcoma lung metastases is mediated by enhancing the sensitivity of the tumor cells to the constitutive FasL in the lung.